Controlled violation of temporal process constraints – Models, algorithms and results. (March 2017) - Kumar, Akhil; Barton, Russell R.
Abstract: While there has been much work on modeling and analysis of temporal constraints in workflows in the context of many real-world applications, there has not been much work on managing violations of temporal constraints. In real-time workflows, such as in medical processes and emergency situations, and also in logistics, finance and in other business processes with deadlines some violations are unavoidable. Here we introduce the notion of controlled violations as the ability to monitor a running process and develop an approach based on constraint satisfaction to determine the best schedule for its completion in a way so as to minimize the total penalty from the violations. The violations are evaluated in terms of metrics like number of violations, delay in process completion, and penalty of weighted violations. We also relate our work to the concept of controllability in literature and show how it can be checked using our method. Finally, we analyze the properties of our approach and also offer a proposal for implementation. Highlights: First, we develop and illustrate a new approach to temporal workflow consistency. Second, we introduce the notion of controlled violations of temporal constraints. Third, we relate our work to earlier work on controllability. Fourth, we discuss correctness and completeness aspects of our approach. Finally, we describe a spread-sheet based implementation of our approach.